Suburbanization processes of the Gödöllő Hillside - Demény, Krisztina (JOURNAL OF LANDSCAPE ECOLOGY, 2008)
New tendencies of the mobility and migration showed up in the agglomeration of Budapest after the transformation of the political system. The most protruding migrations were observed between the capital and Pest County. The population of the surrounding area of Budapest has increased significantly, caused by the migration from Budapest. These facts demonstrate the suburbanization processes well. During the 1990’s, the number of flats has also expanded which followed the increasing number of the enterprises. In this paper, these processes are detailed as studied in the Gödöllő Hill region. This region was chosen because of its vicinity to Budapest. The settlements show several significant changes of their characteristic figures (migration balance, number of inhabitants, housing stock and enterprises) between 1990 and 2006. The changes had started moderately during the first part of the 1990’s, but the process has accelerated significantly since the second part of that decade. The most pronounced transformations have occurred in settlements in the northern and middle parts of the region, which have close proximity to the capital and good traffic conditions.
Keywords: Gödöllő Hill; suburbanization; migration; change in flat stock